2020
DOI: 10.5812/ijem.100870
|View full text |Cite
|
Sign up to set email alerts
|

LT4 and Slow Release T3 Combination: Optimum Therapy for Hypothyroidism?

Abstract: Context: Levothyroxine (LT4) is recommended as replacement therapy for thyroid hormone deficiency. However, some hypothyroid patients receiving LT4 therapy do not feel as well as healthy subjects. This article aimed to review current knowledge regarding LT4 monotherapy versus LT4+LT3 combination therapy and propose future directions regarding LT4+slow release T3 combination treatment for hypothyroidism. Evidence Acquisition: We searched PubMed and Scopus using related keywords. Results: The LT4 monotherapy cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…However, the identification of patients with persistent hypothyroidism symptoms who may need a combination of L-T4 plus L-T3 is daunting due to the non-specificity of the symptoms of hypothyroidism. Whether the combination of L-T4 with L-T3 yields a benefit for a subset of patients is yet to be proven [ 56 , 57 , 58 , 59 ]. Preliminary data show that non-oncological patients with hypothyroidism who carry at least one Thr92Ala-DIO2 polymorphism allele, resulting in lower serum T3 levels, may derive clinical benefit from a combination therapy [ 59 ].…”
Section: Treatment Of Hypothyroidism In Patients With Solid Non-thyro...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the identification of patients with persistent hypothyroidism symptoms who may need a combination of L-T4 plus L-T3 is daunting due to the non-specificity of the symptoms of hypothyroidism. Whether the combination of L-T4 with L-T3 yields a benefit for a subset of patients is yet to be proven [ 56 , 57 , 58 , 59 ]. Preliminary data show that non-oncological patients with hypothyroidism who carry at least one Thr92Ala-DIO2 polymorphism allele, resulting in lower serum T3 levels, may derive clinical benefit from a combination therapy [ 59 ].…”
Section: Treatment Of Hypothyroidism In Patients With Solid Non-thyro...mentioning
confidence: 99%
“…Whether the combination of L-T4 with L-T3 yields a benefit for a subset of patients is yet to be proven [ 56 , 57 , 58 , 59 ]. Preliminary data show that non-oncological patients with hypothyroidism who carry at least one Thr92Ala-DIO2 polymorphism allele, resulting in lower serum T3 levels, may derive clinical benefit from a combination therapy [ 59 ].…”
Section: Treatment Of Hypothyroidism In Patients With Solid Non-thyro...mentioning
confidence: 99%
“…Hypothyroidism, the inevitable outcome of total thyroidectomy and ablative RAI therapy, necessitates thyroid hormone replacement that is associated with some difficulties to mimic the physiological status of thyroid function (52,53). The findings of a Swedish randomized trial of 179 patients with Graves' hyperthyroidism and followup duration of 4 -10 years to compare the three therapeutic options showed that ATD use for 18 months was associated with the highest relapse rate.…”
Section: Comparison Of Different Therapeutic Modalities For Graves' Hyperthyroidismmentioning
confidence: 99%
“…The non-conclusive results, besides heterogeneity in the study population, design, and dosage, may be attributed to the concerns and challenges regarding available oral T3 preparations stemming from the short half-life of T3 with rapid T3 absorption followed by fast metabolization [ 14 17 ]. Despite the lack of definite evidence for the superiority of combination therapy, this strategy remains a common practice in hypothyroid patients who remained dissatisfied with LT4 monotherapy, while the use of LT4 + SR-T3 was suggested [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%